2020
DOI: 10.1111/apps.12254
|View full text |Cite
|
Sign up to set email alerts
|

Identity Continuity Protects Academic Performance, Retention, and Life Satisfaction among International Students

Abstract: International students transitioning to university undergo dramatic changes in social identity, with a need to adapt to a new culture, language, environment, and way of living. This paper explores the impact of this social identity change on academic performance, academic retention, mental health, and life satisfaction. The Social Identity Model of Identity Change (SIMIC) predicts that during life transitions of this form, an individual’s group memberships and associated social identities can protect them from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 71 publications
3
35
1
Order By: Relevance
“…First, our results underline the importance of people's sense of social identity continuity (e.g., Sani et al, 2008;Herrera et al, 2011) for employees' well-being in times of crisis and disruption. In this regard, our research also expands upon previous research that has highlighted the importance of social identity continuity for well-being during major life changes such as transitioning to university life (Iyer et al, 2009), recovering from collective trauma (Muldoon et al, 2017), becoming a mother (Seymour-Smith et al, 2017), retiring from work (Steffens et al, 2016), moving overseas (Cruwys et al, 2020), and recovering from illness (Haslam et al, 2008; for a review, see Haslam et al, 2021). Like many of these transitions, the disruptive changes brought about by COVID-19 have meant this has been a life-changing "once-in-a-lifetime" event and in this context, too, it appears that the maintenance of workgroup memberships has had a significant role to play in reducing people's loneliness and helping to sustain their life satisfaction.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 58%
“…First, our results underline the importance of people's sense of social identity continuity (e.g., Sani et al, 2008;Herrera et al, 2011) for employees' well-being in times of crisis and disruption. In this regard, our research also expands upon previous research that has highlighted the importance of social identity continuity for well-being during major life changes such as transitioning to university life (Iyer et al, 2009), recovering from collective trauma (Muldoon et al, 2017), becoming a mother (Seymour-Smith et al, 2017), retiring from work (Steffens et al, 2016), moving overseas (Cruwys et al, 2020), and recovering from illness (Haslam et al, 2008; for a review, see Haslam et al, 2021). Like many of these transitions, the disruptive changes brought about by COVID-19 have meant this has been a life-changing "once-in-a-lifetime" event and in this context, too, it appears that the maintenance of workgroup memberships has had a significant role to play in reducing people's loneliness and helping to sustain their life satisfaction.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 58%
“…This also shows that social identity maintenance is a crucial challenge for international students in China. The study affirmed that if there is a decline in connection with previous support groups, people will experience a sense of identity loss that will be problematic in the transition (Cruwys et al, 2020; Gu, Schweisfurth, & Day, 2010; Haslam et al, 2008; Iyer et al, 2009; Jetten et al, 2015). These findings provide novel insights to SIMIC that the absence of channels, especially communication technologies, hinder association with previous social networks, leading to potential identity threats.…”
Section: Discussionmentioning
confidence: 80%
“…The loss of social identity affects peoples’ well‐being (Jetten, Haslam, Iyer, & Haslam, 2009). In general, sojourners face unfamiliar education systems, intercultural encounters and sociocultural adjustment (Cruwys, Ng, Haslam, & Haslam, 2020; Colleen Ward et al, 2020). These factors can impact international students’ adaptation and often cause isolation from the host society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, prior work has suggested that wellbeing is often compromised by events such as trauma, brain injury, or migration (Haslam et al, 2021;Jones et al, 2011). Even putatively positive events -such as starting university, becoming a mother, and transitioning to retirement -often threaten wellbeing, with a substantial minority of people struggling to adjust (Cruwys et al, 2020;Lam et al, 2018). Prior research suggests that these difficulties are due, in large part, to the loss and change in the social groups and identities that life transitions entail.…”
Section: Discussionmentioning
confidence: 99%